EFEKTIVITAS FUNGSI LEMBAGA PERLINDUNGAN ANAK INDONESIA (LPAI) PROVINSI ACEH DALAM MELINDUNGI ANAK YANG MENJADI KORBAN TINDAK KEKERASAN - Marzuki Marzuki; Mariati Mariati (Universitas Jabal Ghafur, 2022)
Study Implementation Task Child Protection Agency Indonesia (LPAI) West Sumatra In Protecting Children Becoming Victims of Violence. This study aims to gain anything just as well as procedures for the implementation of tasks Child Protection Agency (LPA) West Sumatra in protecting children who are victims of violence, and whether it has been implemented according to its function. In this study, the problems studied were: (1) How Implementation Child Protection Agency (LPA) West Sumatra, (2) constraints faced by the Institute PerlindunganAnak (LPA) West Sumatra, (3) What efforts do Child Protection Agency (LPA) West Sumatra. The research method used is descriptive method of qualitative research in the form of words written or spoken of those who observed. Based on the results of this study concluded that the task of Child Protection Institution (LPA) West Sumatra in protecting children who are victims of violence carried out by means of advocacy or legal channels, Mediation, Rehabilitation. LPA Sumbar've done our best efforts, although not all cases are handled (from 57 cases were observed only 32 were handled), due to various constraints. To the Child Protection Agency (LPA) West Sumatra has attempted to overcome these constraints, such as the cooperation with relevant agencies, such as social Department. Keywords: Task LPA, Role of Government, cases of violence against children